Global Financial Transmission into Sub-Saharan Africa : A Global Vector Autoregression Analysis - Canales Kriljenko, Jorge (IMF Working Papers; Working Paper ;, 2014)
Sub-Saharan African countries are exposed to spillovers from global financial variables, but the impact on economic activity is more significant in more financially developed economies. Generalized impulse responses from a GVAR exercise demonstrate how the CBOE volatility index (VIX) and credit conditions around the globe impact a subset of sub-Saharan African economies and regions. The estimated relationships suggest that the effect of global uncertainty is more pervasive in exports, with the impact on economic and lending activities being mixed. The channels of transmission include the effects of global financial variables on commodity prices and on trading-partner's macroeconomic and financial variables. The analysis suggests that shocks to credit conditions in the euro area and the U.S. have not significantly affected local lending conditions or economic activity in sub-Saharan Africa during 1991-2011, except perhaps in South Africa.